2011
DOI: 10.1080/17452759.2010.491938
|View full text |Cite
|
Sign up to set email alerts
|

Protective coating materials on nylon substrate by sol–gel

Abstract: The solÁgel process can be used to coat a nylon substrate, changing the properties of the material and the interaction between the coating and the substrate takes place through the NH groups of nylonThe application of thin films as coating on several surfaces has been one of the major factors responsible for technological advances. Additive Manufacturing is used to define a set of technologies that have the building of 3D physic prototypes as a common characteristic. In this work we have studied the properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 21 publications
0
7
1
2
Order By: Relevance
“…In a previous work, we had observed that the decomposition temperature of the ABS polymer increased after coating with different compositions of sols. 23,24 Indeed, in the present work the decomposition temperature maximum changed from 417°C for ABS alone to 429 and 421°C for the ABS (ac.) complex and the ABS (bc.)…”
Section: Photoluminescence (Pl)mentioning
confidence: 87%
“…In a previous work, we had observed that the decomposition temperature of the ABS polymer increased after coating with different compositions of sols. 23,24 Indeed, in the present work the decomposition temperature maximum changed from 417°C for ABS alone to 429 and 421°C for the ABS (ac.) complex and the ABS (bc.)…”
Section: Photoluminescence (Pl)mentioning
confidence: 87%
“…Outras bandas podem também ser observadas no espectro em 1454 (dNC'H), 1384 (dCH), 1298 (nCN), 1100 e 1064 (nCC), 936 (nNC), e 635 cm -1 (dOCN). 16,38,39…”
Section: Espectroscopia De Absorção Ramanunclassified
“…As temperaturas máximas de decomposição sofreram aumento de 442 o C para a PA, 444 o C PA+Ox e 448 o C PA+Ox+PI, indicando a influência na estabilidade térmica da membrana de PA, propriedade observada na literatura. 13,15,16 A Figura 9 mostra as curvas DSC para das membranas de PA, PA+Ox e PA+Ox+PI.…”
Section: Análise Térmica Termogravimetria (Tga) E Sua Derivada (Dtg)unclassified
“…After 2 h of agitation, the sol was deposited onto PA by dip-coating, as described in literature. 23 The substrates remained in the sols for 20 min, followed by drying at 50° C for 1 day.…”
Section: Polyamide Coatingmentioning
confidence: 99%